Cyberspace Enhanced Payment Systems in the Zimbabwean Retail Sector: Opportunities and Threats - Mugari, Ishmael (International Journal of Economics and Financial Issues, 2017)
The cyberspace has revolutionised payment systems across the globe. The retail sector has also embraced cyberspace enhanced payment systems as an alternative or compliment to the conventional cash based payment systems. Whilst the cyberspace has brought positive results to the business environment, new criminal threats have also evolved. This study sought to explore the nature of cyberspace enhanced payment systems for the retail sector in Zimbabwe, as well as to document the nature of cyber threats to this sector. It was found out that use of debit cards, mobile money transfers and RTGS transactions top the list of cyberspace enhanced payment systems in the Zimbabwean retail sector. Dominant cyber threats to the retail sector include infection of computers with viruses and unauthorised access, whilst debit card fraud and fraudulent RTGS transactions infrequently occur in the Zimbabwean retail sector. Keywords: Cybercrime, e-payments, payment fraud JEL Classifications: E42, L81